Genome-Wide Profiling of Circular RNAs in the Rapidly Growing Shoots of Moso Bamboo (Phyllostachys edulis). (5th March 2019) - Wang, Yongsheng; Gao, Yubang; Zhang, Hangxiao; Wang, Huihui; Liu, Xuqing; Xu, Xi; Zhang, Zeyu; Kohnen, Markus V; Hu, Kaiqiang; Wang, Huiyuan; Xi, Feihu; Zhao, Liangzhen; et al.
Abstract: Circular RNAs, including circular exonic RNAs (circRNA), circular intronic RNAs (ciRNA) and exon-intron circRNAs (EIciRNAs), are a new type of noncoding RNAs. Growing shoots of moso bamboo ( Phyllostachys edulis ) represent an excellent model of fast growth and their circular RNAs have not been studied yet. To understand the potential regulation of circular RNAs, we systematically characterized circular RNAs from eight different developmental stages of rapidly growing shoots. Here, we identified 895 circular RNAs including a subset of mutually inclusive circRNA. These circular RNAs were generated from 759 corresponding parental coding genes involved in cellulose, hemicellulose and lignin biosynthetic process. Gene co-expression analysis revealed that hub genes, such as DEFECTIVE IN RNA-DIRECTED DNA METHYLATION 1 ( DRD 1), MAINTENANCE OF METHYLATION ( MOM ), dicer-like 3 ( DCL3 ) and ARGONAUTE 1 ( AGO1 ), were significantly enriched giving rise to circular RNAs. The expression level of these circular RNAs presented correlation with its linear counterpart according to transcriptome sequencing. Further protoplast transformation experiments indicated that overexpressing circ - bHLH93 generating from transcription factor decreased its linear transcript. Finally, the expression profiles suggested that circular RNAs may have interplay with miRNAs to regulate their cognate linear mRNAs, which was further supported by overexpressing miRNA156 decreasing the transcript of circ-TRF-1 and linear transcripts of TRF-1 . Taken together, the overall profile of circular RNAs provided new insight into an unexplored category of long noncoding RNA regulation in moso bamboo.